Degradation of azinphos-methyl and chlorpyrifos from aqueous solutions by ultrasound treatment - Agarwal, Shilpi; Tyagi, Inderjeet; Gupta, Vinod Kumar; Dehghani, Mohammad Hadi; Bagheri, Amin; Yetilmezsoy, Kaan; Amrane, Abdeltif; Heibati, Behzad; Rodriguez-Couto, Susana (ELSEVIER SCIENCE BV, 2016)
Azinphos-methyl and chlorpyrifos are the organophosphorous pesticides which pose serious threats to the environment including their detrimental effect on humans and, therefore, their removal from the environment is a must. Hence, in the present paper the ultrasound technique was applied to remove the above-mentioned hazardous compounds. For this, the effect of influential parameters such as pH, initial pesticide concentration, frequency, electric power and treatment time on the ultrasound degradation of azinphos-methyl and chlorpyrifos was well investigated and elucidated. The results obtained showed that azinphos-methyl and chlorpyrifos were effectively and rapidly degraded by the ultrasound technique. Thus, the operating optimal conditions (initial pH 9, initial pesticide concentration 1 mg/L, frequency 130 kHz, electric power 500 Wand treatment time 20 min) lead to a degradation of 78.50% for azinphos-methyl and of 98.96% for chlorpyrifos with in 20 min of contact time. Two multiple regression-based equations were derived to describe the degradation process of the pesticides by the ultrasound treatment. The result of this study showed that the-polynomial equations satisfactorily described the behavior of the present process for various operating conditions. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Azinphos methyl; Chlorpyrifos; Phosphorous pesticides; Ultrasound; Degradation; BAGASSE FLY-ASH; WASTE-WATER; ACTIVATED CARBON; TITANIUM-DIOXIDE; SUGAR-INDUSTRY; GRAPHENE OXIDE; P-NITROPHENOL; BOTTOM ASH; REMOVAL; DIAZINON; Chemistry; Physics